2021
DOI: 10.3390/ijerph18116118
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Response to Three Types of Urban Spaces before and after Lockdown during the COVID-19 Pandemic

Abstract: (1) Background: Prolonged lockdowns with stay-at-home orders have been introduced in many countries since the outbreak of the COVID-19 pandemic. They have caused a drastic change in the everyday lives of people living in urbanized areas, and are considered to contribute to a modified perception of the public space. As research related to the impact of COVID-19 restrictions on mental health and well-being emerges, the associated longitudinal changes of brain hemodynamics in healthy adults remain largely unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…The COVID‐19 pandemic was found to cause hemodynamic changes in the brain and impairment in olfactory function. 84 , 85 This study mainly used self‐reported questionnaires to measure psychiatric symptoms and did not make clinical diagnosis. The gold standard for establishing psychiatric diagnosis involved structured clinical interview and functional neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID‐19 pandemic was found to cause hemodynamic changes in the brain and impairment in olfactory function. 84 , 85 This study mainly used self‐reported questionnaires to measure psychiatric symptoms and did not make clinical diagnosis. The gold standard for establishing psychiatric diagnosis involved structured clinical interview and functional neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…Despite, the women are overrepresented in depression even prior to the pandemic. 76 Another limitation is that the COVID-19 pandemic was found to cause hemodynamic changes in the brain. 77 This study mainly used selfreported questionnaires to measure psychiatric symptoms and did not make clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 , 41 Olszewska‐Guizzo and colleagues found decreased brain haemodynamics during the COVID‐19 pandemic which is associated with depressive symptoms. 42 As such, future research is required to assess a subset of participants, using functional neuroimaging and clinical diagnosis, for associated lockdown depression, may be warranted. Lastly, as mentioned previously, our data collection was undertaken towards the tail end of the lockdown.…”
Section: Discussionmentioning
confidence: 99%